Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(A=\frac{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2014}}{\frac{2013}{1}+\frac{2012}{2}+\frac{2011}{3}+...+\frac{1}{2013}}\)
\(A=\frac{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2014}}{\left(\frac{2012}{2}+1\right)+\left(\frac{2011}{3}+1\right)+...+\left(\frac{1}{2013}+1\right)+1}\)
\(A=\frac{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2014}}{\frac{2014}{2}+\frac{2014}{3}+...+\frac{2014}{2013}+\frac{2014}{2014}}\)
\(A=\frac{\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2014}}{2014.\left(\frac{1}{2}+\frac{1}{3}+\frac{1}{4}+...+\frac{1}{2014}\right)}\)\
\(A=\frac{1}{2014}\)
`A = 2 + 2^2+ ... + 2^2017`
`=> 2A = 2^2 + 2^3 + ... + 2^2018`
`=> 2A - A = (2^2 + 2^3 + ... + 2^2018) - (2 + 2^2 + ... +2^2017)`
`=> A = 2^2018 - 2`
`B = 1 + 3^2 + ... + 3^2018`
`=> 3^2B = 3^2 + 3^4 + ... + 3^2020`
`=> 9B-B =(3^2 + 3^4 + ... + 3^2020) - (1 + 3^2 + ... + 3^2018`
`=> 8B = 3^2020 - 1`
`=> B = (3^2020 - 1)/8`
`C = 5 + 5^2 - 5^3 + ... + 5^2018`
`=> 5C = 5^2 + 5^3 - 5^4 + ... +5^2019`
`=> 5C + C = ( 5^2 + 5^3 - 5^4 + ... 5^2019) + (5 + 5^2 - 5^3 + ... + 5^2018)`
`=> 6C = 55 + 5^2019`
`=> C = (5^2019 + 55)/6`
B = (1 + 1/2)(1 + 1/3)(1 + 1/4) ...(1 + 1/100)
= \(\frac{3}{2}.\frac{4}{3}.\frac{5}{4}...\frac{101}{100}\)
= \(\frac{3.4.5....101}{2.3.4...100}=\frac{101}{2}\)
C = \(\left(1-\frac{1}{2}\right)\left(1-\frac{1}{3}\right)\left(1-\frac{1}{4}\right)....\left(1-\frac{1}{1000}\right)\)
\(=\frac{1}{2}.\frac{2}{3}.\frac{3}{4}....\frac{999}{1000}\)
\(=\frac{1.2.3...999}{2.3.4....1000}=\frac{1}{1000}\)
S=1−2+2^2+2^3+...+2^2000
2S=2−2^2+2^3−2^4+...+2^2001
⇒2S-S=2^2001-1
⇒S=.................................
Ta có : S=1-2+22-23+...+21000
=>2S=2-22+23-24+...+21001
=>3S=1+21001
=>S=\(\frac{1+2^{1001}}{3}\)
Đặt A = 21000 - 2999 - 2998 -....- 22 - 2 - 1
A = 21000 - (2999 + 2998 +....+ 22 + 2 + 1)
Đặt B = 2999 + 2998 +...+ 22 + 2 + 1 (1)
2B = 21000 + 2999 +....+ 23 + 22 + 2 (2)
Lấy (2) trừ (1) ta được
B = 21000 - 1
=> A = 21000 - B = 21000 - (21000 - 1) = 21000 - 21000 + 1 = 0 + 1 = 1
Vậy A = 1
A=2^2005-(2^2004+2^2003+...+2+1)
đặt A=2^2004+2^2003+...+2+1
2A=2(1+2+...+2^2004)
2A=2+2^2+2^2005
2A=2+2^2+...+2^2005
A=2^20052005-1 khi đó A=2^2005-A
suy ra A=2^2005-(2^2005-1)=2^2005-2^2005+1=1
CHÚC BẠN HỌC TỐT ##
A = 1² + 2² + 3² + ... + 1000²
= 1000.(1000 + 1).(2.1000 + 1) : 6
= 1000.1001.2001 : 6
= 333833500